Macroeconomic Approach to Point in Time Probability of Default Modeling – IFRS 9 Challenges - Đurović Andrija (Journal of Central Banking Theory and Practice, 2019)
This paper aims to present one possible retail estimation framework of lifetime probability of default in accordance with IFRS 9. The framework rests on “term structure of probability of default” conditional to given forward-looking macroeconomic dynamics. Due to the one of the biggest limitation of forward-looking modelling – data availability, model averaging technique for quantification of macroeconomic effect on default probability is explained.